DYNAMICS OF COMPETITIVENESS AND MARKET POSITION OF INDONESIAN COCONUT SHELL CHARCOAL EXPORTS IN THE INTERNATIONAL MARKET - Putri, Lovina Aresta; Syaukat, Yusman; Feryanto, Feryanto (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Along with the energy and environmental pollution problems, demand for coconut shell charcoal in the international market has experienced an increasing trend in the last decade. However, the value of Indonesian exports of coconut shells frequently experiences fluctuating conditions. Seeing the increasing demand for this product and the intense competition between producing countries in the international market, shows that Indonesian coconut shell charcoal has the potential to be developed. This research aims to analyze the dynamics of competitiveness and market position of Indonesian coconut shell charcoal exports in ten major export destination countries (Saudi Arabia, South Korea, Japan, Iraq, China, Türkiye, Germany, Lebanon, United Arab Emirates, and Netherlands) using the Dynamic Revealed Comparative Advantage (DRCA) method. The DRCA analysis findings indicate that, in the ten major export destination countries, the dynamics of Indonesia's coconut shell charcoal exports competitiveness shows a fluctuating state with the best export competitiveness dynamic position in the South Korean and Japanese markets. However, the export market position of Indonesian coconut shell charcoal has also decreased from a Rising Star in Period I (2010–2014) to Leading Retreat in Period III (2019–2022). The implication is that Indonesian coconut shell charcoal products are stated to have weak export competitiveness in the main export destination countries. Therefore, export-oriented competitiveness development strategies such as improving the product quality, increasing effective promotion and marketing efforts, and improving market access are very necessary to strengthen Indonesian coconut shell charcoal's competitive position in export destination countries.